A Curious Case of Flower Phobia: Anthophobia - Saimbi, Desiree; Sarmah, Shabdita R.; Kumar, Atmesh; Shivalkar, Rupali P.; Prasad, Sanjeeta (Annals of the National Academy of Medical Sciences (India), 2017)
Fears, anxieties and speciﬁc phobias are classiﬁed as internalizing behavior problems. The development of speciﬁc phobias may result from the pairing of a speciﬁc object or situation with the emotion of fear. Flowers are usually perceived as pleasant stimulus, producing a relaxing effect on our mind and body, but here we present a rare case, wherein ﬂowers are perceived as a malevolent stimulus and producing phobic anxiety in an eleven-year old boy, leading to avoidance behaviors and much interference in normal functioning. He was diagnosed to have Speciﬁc Phobia of natural environment type with Somnambulism and treated with SSRI (escitalopram) and Behavior Therapy (systematic desensitization). Over a period of eight months his symptoms remitted completely and he maintained the remission for now one year with no further intervention.
Keywords: Childhood fear; phobias; anxiety; behavior therapy; ﬂowers fear